Effects of nitrogen fertilizer on dry matter and nitrogen yields of herbaceous legumes in interior Alaska - Panciera, M. T.; Sparrow, S. D. (Canadian Journal of Plant Science, 1995)
Birdsfoot trefoil (Lotus corniculatus L.), arrowleaf clover (Trifolium vesiculosum Savi.), berseem clover (Trifolium alexandrinum L.), crimson clover (Trifolium incarnatum L.), barrel medic (Medicago truncatula Gaertn.), winter vetch (Vicia villosa subsp. varia L.), flatpea (Lathyrus tingitanus L.), red clover (Trifolium pratense L.), alfalfa (Medicago sativa L.), sweetclover (Melilotus officinalis Lam.), fababean (Vicia faba L.), field pea (Pisum sativum subsp. arvense L.) and white lupin (Lupinus alba L.) were grown for 2 yr in interior Alaska to assess their potential as forage and green manure crops and to evaluate the effects of N fertilizer on legume performance. Herbage yield, crude protein, and total N yield were the criteria used. In addition to previously identified promising species, berseem clover, arrowleaf clover, winter vetch and flatpea consistently produced over 3 t ha −1 of herbage and accumulated over 67 kg N ha −1 . Nitrogen fertilizer (90 kg N ha −1 ) improved yields of arrowleaf clover and winter vetch at Fairbanks (5344 vs. 3685 kg ha −1 ), but N fertilization depressed yields at Delta Junction. Forage crude protein for the promising species ranged from 120 to 220 g kg −1 . Several species exhibited adequate tolerance of low soil pH to be grown on acid soils without liming. Key words: Forage legume crops, Alaska, N fertilization, subarctic